Legal appraisal of the Pesticides Act 1974 in controlling the sale of pesticides raw material in combating illegal pesticides / Nazli Mat Aris - Mat Aris, Nazli (2018)
Dumping of illegal pesticides in the market and being used by the farmer becoming a growing concern. The quality of the pesticides has become the disputed matter among the user. The problem cannot be solving just by enforcing the existing provision in the law at the retailer and user level only. There is a need to look at the different angle and at the source of point how the illegal pesticide been produced. This dissertation is look on the Pesticides Act 1974 and the issue related to the control of pesticides raw material in combating illegal pesticides. This dissertation looks also on the effectiveness of current pesticides Act 1974 in adequate the right way in managing pesticides. This dissertation focuses on the requirement to control pesticides raw material in assuring the quality of pesticide product in the market. This dissertation is based on doctrinal research and finding from interview session with expert respondents in pesticides stakeholders. The result of the study suggested that the current law need to be reform and new provision should be insert to the current law to enhance the law and at same time will reducing the illegal pesticides in the market. It is hope that this study can contribute to the improvement of the pesticide management in Malaysia.